Cáncer de mama y disfunción sexual femenina: análisis en una muestra de mujeres peruanas adultas - Pasapera-Rivera, Manuel (2019)
Introduction: Sexuality is a complex area in women, especially in those who have been diagnosed with breast cancer (BC). Objective: To evaluate whether there is an association between breast cancer (BC) and sexual dysfunction (SD) in adult women in a national reference hospital of Social Security in Peru. Method and sample: We carried out an analysis in 167 women under 60 years of age, which were divided into two groups: with BC (after mastectomy and without mastectomy), and without cancer. We used the validation of the Spanish version of the Female Sexual Dysfunction Index. We made a comparison among women with BC and without cancer (A). Additionally, we carried out two exploratory comparisons: among women with BC after mastectomy and without mastectomy (B); and another among women without BC, with BC after mastectomy, and with BC without mastectomy (C). We estimated crude prevalence ratios (cPR) and adjusted prevalence ratios (aPR) with 95% CI using generalized lineal Poisson regression models with a non-parametric bias-corrected and accelerated boostrap. Results: The frequencies of SD were 95,7%; 43,8% and 35,1% in women with BC after mastectomy; with BC without undergoing mastectomy and without cancer, respectively. In A, it was observed that women with BC presented a higher probability of SD than those without cancer (cPR:1.86; CI95%:1,27–2,72/ aPR:1,51; CI95%:1,06–2,15). In B, it was evidenced that, among women with BC, those after mastectomy had a higher probability of SD (cPR:2,19; CI95%: 1,63–2,92/ aPR:1,62; CI95%: 1,26–2,08). In C, a higher probability of SD was identified in women with BC after mastectomy versus women without cancer (cPR 2,73; CI 95%: 1,88–3,94/ aPR:1,93; CI 95%: 1,32–2,80). Conclusion and recommendation: The frequency of SD is higher in women with breast cancer and, in this group, the probability is higher in women with mastectomy antecedents. In this group of women, the sexual sphere should be explored in the clinical practice.